Clinical features of diabetic patients referred by general physicians due to less ophthalmic examinations - Otsu Y (Dove Medical Press, 2014)
Yayoi Otsu, Masato Matsuoka, Kayako Matsuyama, Tetsuya Nishimura Department of Ophthalmology, Kansai Medical University, Takii Hospital, Osaka, Japan Background: The purpose of this study was to determine the clinical features of patients with type 2 diabetes, and less ophthalmic examinations, referred by general physicians to ophthalmologists. Methods: The medical charts of 327 patients with type 2 diabetes referred to our department from general physicians were reviewed. A detailed medical history was taken and a complete ophthalmic examination was performed for all patients. The patients were divided into two groups, ie, those with a history of missing ophthalmic examinations for more than a year (noncompliant group) and those with no previous ophthalmic examinations (never-examined group). Serum levels of glycosylated hemoglobin and creatinine, estimated glomerular filtration rate, and urine albumin/creatinine ratio were obtained from medical records. Results: Of the 327 patients, 102 had diabetic retinopathy (31.2%), with a mean best-corrected visual acuity of 0.037±0.36 logMAR (logarithm of the minimum angle of resolution) units. Of the 327 patients, 203 were in the never-examined group and 124 were in the noncompliant group. The incidence of diabetic retinopathy in the noncompliant group was significantly higher than that in the never-examined group (P<0.001). Best-corrected visual acuity in the noncompliant group was significantly worse than in the never-examined group (P=0.004). Glycosylated hemoglobin levels and estimated glomerular filtration rate in the noncompliant group were significantly lower than in the never-examined group (P<0.001 and P<0.003, respectively); serum creatinine levels and urine albumin/creatinine ratio were significantly higher (P=0.020 and P=0.001, respectively). The severity of the diabetic retinopathy was significantly correlated with compliance in terms of ophthalmic examinations and with urine albumin/creatinine ratio (multiple regression analysis, P=0.047 and P<0.001, respectively). Conclusion: Our results show that diabetic patients referred from general physicians due to less ophthalmic examinations generally have good visual acuity, but one third of them have diabetic retinopathy. A history of missing ophthalmic examinations and albuminuria are risk factors for diabetic retinopathy. Keywords: diabetic retinopathy, general physician, ophthalmologists, albuminuria